Analysis of the administrative management at the Local Educational Management Unit N.° 302, Leoncio Prado - López-López, Alan D. (2022)
Objective: To analyze the administrative management in the Local Educational Management Unit N.° 302, Leoncio Prado. Methods. The research approach was quantitative, while the level was descriptive. A survey was applied to the principals (primary and secondary) that make up the educational staff of the province of Leoncio Prado, who formed the unit of analysis of the study. Results. In the analysis of administrative management, the results were 42.0 % or "regular". Planning yielded results of 46.1 % or "fair". Also, organization yielded results of 47.7 % or "fair". The results for management were 47.2 % or "fair". Finally, the results for control were 47.2 % or "fair". Conclusions. The analysis of the administrative management of the institution was predominantly regular, being the dimensions: planning, organization, direction and control, the ones that presented the greatest deficiencies in the management of the Local Educational Management Unit N.° 302, Leoncio Prado.